2009
DOI: 10.1007/s00330-009-1593-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraobserver variability of MR arthrography in the detection and classification of superior labral anterior posterior (SLAP) lesions: evaluation in 78 cases with arthroscopic correlation

Abstract: MR arthrography allows reliable and accurate detection of SLAP lesions. In addition, SLAP lesions can be diagnosed and classified with substantial to excellent inter- and intraobserver agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 16 publications
5
17
0
Order By: Relevance
“…The results of our study were concordant with the high diagnostic performance of multidetector CT arthrography reported in prior studies ( 9,19 ). In terms of interobserver agreement, detection of SLAP lesions at multidetector CT arthrography showed excellent agreement, similar to MR arthrography ( 18 ). In our study, the percentage of the correct classifi cation of SLAP lesions for both readers was similar to that of MR arthrography ( 15,17,18 ).…”
Section: Musculoskeletal Imaging: Superior Labral Anteroposterior Tearssupporting
confidence: 91%
See 3 more Smart Citations
“…The results of our study were concordant with the high diagnostic performance of multidetector CT arthrography reported in prior studies ( 9,19 ). In terms of interobserver agreement, detection of SLAP lesions at multidetector CT arthrography showed excellent agreement, similar to MR arthrography ( 18 ). In our study, the percentage of the correct classifi cation of SLAP lesions for both readers was similar to that of MR arthrography ( 15,17,18 ).…”
Section: Musculoskeletal Imaging: Superior Labral Anteroposterior Tearssupporting
confidence: 91%
“…In terms of interobserver agreement, detection of SLAP lesions at multidetector CT arthrography showed excellent agreement, similar to MR arthrography ( 18 ). In our study, the percentage of the correct classifi cation of SLAP lesions for both readers was similar to that of MR arthrography ( 15,17,18 ). In terms of interobserver agreement, classifi cation of SLAP lesions at multidetector CT arthrography showed good agreement ( 18 ).…”
Section: Musculoskeletal Imaging: Superior Labral Anteroposterior Tearssupporting
confidence: 76%
See 2 more Smart Citations
“…In another study also assessing the determining interobserver and intraobserver variability of MR arthrography in the detection and classification of SLAP lesions, Holzapfel et al [24] found that MR arthrography allowed reliable and accurate detection of SLAP lesions. In addition, they proved that SLAP lesions could be diagnosed and classified with substantial to excellent interobserver and intraobserver agreement.…”
Section: Discussionmentioning
confidence: 99%